Strontium vanadium oxide-hydrides: "square-planar" two-electron phases. - Denis Romero, F; Leach, A; Möller, J; Foronda, F; Blundell, S; Hayward, M (Wiley, 2014)
A series of strontium vanadium oxide-hydride phases prepared by utilizing a low-temperature synthesis strategy in which oxide ions in Sr(n+1)V(n)O(3n+1) (n=∞, 1, 2) phases are topochemically replaced by hydride ions to form SrVO2H, Sr2VO3H, and Sr3V2O5H2, respectively. These new phases contain sheets or chains of apex-linked V(3+)O4 squares stacked with SrH layers/chains, such that the n=∞ member, SrVO2H, can be considered to be analogous to "infinite-layer" phases, such as Sr(1-x)Ca(x)CuO2 (the parent phase of the high-T(c) cuprate superconductors), but with a d(2) electron count. All three oxide-hydride phases exhibit strong antiferromagnetic coupling, with SrVO2H exhibiting an antiferromagnetic ordering temperature, T(N)>300 K. The strong antiferromagnetic couplings are surprising given they appear to arise from π-type magnetic exchange.